Implementasi Program Penguatan Literasi Qur’ani dan Pembelajaran Keagamaan pada Anak TPA dan Ibu-Ibu Majlis Ta’lim dalam Kegiatan Kuliah Kerja Nyata Rekognisi: Pengabdian - Flora; Amir Hamzah; Yolanda Puteri Maulyza; Aini Hoirunisa; Sarah Qonita; Wahyuni Nabila Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Community Service Program (KKN) can be understood as a form of community service designed to improve the quality of education, particularly in religious aspects. In this paper, the author seeks to describe the implementation of a program aimed at improving Qur’anic literacy and religious education for children at the Qur’an Education Center (TPA) and for mothers at the Majlis Ta’lim. This study employs a descriptive method with a qualitative approach. Data were collected through observation, interviews, and documentation during the KKN activities.The findings of this study indicate that the activities conducted included teaching Qur’an reading, introducing daily prayers, memorizing short surahs, and delivering religious-related materials to the mothers at the Majlis Ta’lim. These activities contributed positively to improving participants’ ability to read the Qur’an, their understanding of religion, and their willingness to engage in the learning process. Furthermore, student participation in this program also played a significant role in strengthening religious values within the surrounding community. Thus, the implementation of the Qur’anic literacy and religious education program through the KKN activities serves as an effective strategy for enhancing the quality of religious education for children and the broader community.